Konsep Desain Jalur Interpretasi Wisata Sejarah Mads Lange di Hilir Tukad Mati Kuta Badung - Sattwika, Ida Nyoman Dwaja; Kohdrata, Naniek; Dharmadiatmika, I Made Agus (Jurnal Arsitektur Lansekap; Vol.9, No.1, April 2023, 2023)
Conceptual Design of Historical Tourism Interpretation Route of Mads Lange in Downstream Tukad Mati Kuta Badung . Downstream of Tukad Mati is a historical location related to the development of Kuta. In the past, this downstream was a pier called Jangkong pier. Mads Lange was known to have businesses that had been part of Kuta development at that time. Mads Lange was a Danish trader who lived in Kuta from 1839 and also died in Kuta in 1856. There are three locations related with Mads Lange in Tukad Mati downstream, those are; the Jangkong former pier associated with the trading activities, the former houses and factories of Mads Lange which are currently become Pasar Senggol Kuta (Kuta community market) and the Alron Hotel, and the Mads Lange’s grave. This study aims to transform the story of Mads Lange during his time in Kuta and adapt it into historical tourism program that is an interpretation route design concept. The research method of this study is a survey method in which the data collected by using observation, interviews and literature studies. Descriptive analysis is used for data processing with four stages: preparation, data inventory, synthesis analysis, and design concepts. The basic concept generated in this research is the utilization of the historical story of Mads Lange as a branding of the tourist interpretation in Tukad Mati downstream. The concept of interpretation facilities is carried out by adding interpretation facilities, such as: interpretation media, information centers, and making a replica of the pier. In addition, supporting facilities are also added speed table, river walk, directions, parking, gates, seating, and a foodcourt. For the lighting concept, namely the concept of welcome light on the gate, guiding light, and lighting for interpretation. The concept of interpretation route is designed by integrating some of existing tourist attractions and some others facilities and elements of design required. The conceptual design of historical route of Mads Lange starts from the gate, information center, Mads Lange grave, Mads Lange chest sclapture, dalmantion dog sclapture, Jangkong replica, river landscape, foodcourt, and ending at the plaza.